A Universal New Definition of Heart Failure With Improved Ejection Fraction for Patients With Coronary Artery Disease - Huang, Haozhang; Liu, Jin; Lei, Min; Yang, Zhou; Bao, Kunming; Li, Qiang; Lai, Wenguang; Wang, Bo; He, Yibo; Chen, Shiqun; Ou, Chun-Quan; Abudukerimu, Maimaitiaili; et al. (Frontiers in Physiology, 2021)
Aims To describe the characteristics and outcomes of the universal new definition of heart failure with improved ejection fraction (HFimpEF) and to identify predictors for HFimpEF among coronary artery disease (CAD) patients. Methods CAD subjects with heart failure reduced ejection fraction (EF) (HFrEF) (EF ≤ 40%) at baseline were enrolled from the real-world registry of the Cardiorenal ImprovemeNt study from January 2007 to December 2018. The new definition HFimpEF was defined as left ventricular EF (LVEF) of ≤ 40% at baseline and with improvement of up to 40% and at least a ≥10% increase during 1 month to 1 year after discharge. Results Of the 747 CAD patients with HFrEF (86.7% males, mean age: 61.4 ± 11 years) and 267 (35.7%) patients conformed to the new HFimpEF definition. HFimpEF patients were younger (aOR: 0.98 [0.97–0.99]) and had a higher rate of hypertension (aOR:1.43 [1.04–1.98]), lower rate of percutaneous coronary intervention (PCI) treatment at the time of detection of HFrEF (aOR: 0.48 [0.34–0.69]), history of PCI (aOR: 0.51 [0.28–0.88]) and history of acute myocardial infarction (aOR: 0.40 [0.21–0.70]), and lower left ventricular end diastolic diameter (aOR: 0.92 [0.90–0.95]). During 3.3-year follow-up, HFimpEF patients demonstrated lower rates of long-term all-cause mortality (13.1% vs. 20.8%, aHR: 0.61[0.41-0.90]). Conclusions In our study, CAD patients with HFimpEF achieved a better prognosis compared to those with persistent HFrEF. CAD patients meeting the criteria for the universal definition of HFimpEF tended to be younger, presented fewer clinical comorbidities, and lower left ventricular end diastolic diameter.